2019
DOI: 10.1101/760330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread Receptor Driven Modulation in Peripheral Olfactory Coding

Abstract: AbstractWe utilized swept confocally aligned planar excitation (SCAPE) microscopy to measure odor-driven activity simultaneously in many (>10,000) olfactory sensory neurons distributed over large areas of intact mouse olfactory epithelium. This approach allowed us to investigate the responses to mixtures or blends of odors and their components, a more realistic stimulus than monomolecular odors. In up to 38% of responding cells, responses to a mixture of odors were different… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Beyond our theoretical observations, there are other more recent experimental studies (in bioRxiv preprints) that report related effects (Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). Our work is unique in the following regard:…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Beyond our theoretical observations, there are other more recent experimental studies (in bioRxiv preprints) that report related effects (Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). Our work is unique in the following regard:…”
Section: Discussionmentioning
confidence: 58%
“…Recent theoretical work has shown that a variety of non-linear interactions among multiple ligands at the same receptor can readily arise with a simple two-step model of receptor activation (Reddy et al, 2018). Experimental work in vitro in OSNs has suggested the existence of non-linear interactions, especially antagonism (Firestein and Shepherd, 1992;Kurahashi et al, 1994;Mathis et al, 2016;Rospars et al, 2008Rospars et al, , 2000Singh et al, 2019) (also bioRxiv preprints; Inagaki et al, 2019;Pfister et al, 2019;Xu et al, 2019). However, the prevalence of these interactions, especially in living animals within the constraints of natural sniffing dynamics, has not been explored.…”
Section: Introductionmentioning
confidence: 99%